Transition of Laboratory Management System Based on ISO/IEC 17025:2017 at SNSU-BSN - Chery Chaen Putri; Melati Azizka Fajria; Adindra Vickar Ega; Eka Pratiwi; Yulita Ika Pawestri; Nelfyenny Nelfyenny; Muhammad Haekal Habibie (Instrumentasi, 2021)
To accommodate current technological developments and laboratory conditions, ISO (International Organization for Standardization) and IEC (International Electrotechnical Commission) published the latest version of the ISO/IEC 17025 standard in 2017. Complying with ISO/IEC 17025:2017 enables laboratory to provide measurement results that are valid and traceable to international unit system. SNSU-BSN as National Metrology Institute (NMI) in Indonesia has transformed its management system from the old version ISO/IEC17025:2005 to the current ISO/IEC 17025:2017 in 2019. This study explains the process of SNSU-BSN transition in order to establish a management system complying with ISO/IEC 17025:2017. A comparison between the implementation of the old and the current ISO/IEC 17025 was explained along with its impacts and benefits.  This study shows that SNSU-BSN as a NMI in Indonesia has successfully implemented the full implementation of the transition from ISO/IEC 17025:2005 to ISO/IEC 17025:2017 in accordance with the time-frame determined by the Joint ILAC-ISO and KAN.